2014
DOI: 10.1111/anae.12634
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of cerebral tissue oxygenation and postoperative cognitive dysfunction among patients undergoing coronary artery bypass grafting randomised to surgery with or without cardiopulmonary bypass*

Abstract: SummaryCoronary artery bypass surgery, performed with or without cardiopulmonary bypass, is frequently followed by postoperative cognitive decline. Near-infrared spectroscopy is commonly used to assess cerebral tissue oxygenation, especially during cardiac surgery. Recent studies have suggested an association between cerebral desaturation and postoperative cognitive dysfunction. We therefore studied cerebral oxygen desaturation, defined as area under the cerebral oxygenation curve < 40% of > 10 min.%, with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 35 publications
3
43
0
5
Order By: Relevance
“…23,24 An additional nine RCTs were excluded as they did not involve the target intervention comparison. [25][26][27][28][29][30][31][32][33][34] Two additional RCTs were excluded because they were published as an abstract 35,36 and one RCT was excluded because although it correlated anesthetic depth with cerebral oximetry, it did not detail the associated intervention. 37 Finally, three additional trials were identified from reference lists of the articles included.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…23,24 An additional nine RCTs were excluded as they did not involve the target intervention comparison. [25][26][27][28][29][30][31][32][33][34] Two additional RCTs were excluded because they were published as an abstract 35,36 and one RCT was excluded because although it correlated anesthetic depth with cerebral oximetry, it did not detail the associated intervention. 37 Finally, three additional trials were identified from reference lists of the articles included.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…We undertook a secondary analysis of data from a published randomised clinical trial that investigated the differences in the incidence and severity of cerebral oxygen desaturation during coronary artery bypass surgery with or without bypass . Study patients underwent coronary artery bypass surgery at the University Medical Centre Groningen, the Netherlands, between June 2011 and May 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, brain NIRS has been used as a marker for cerebral oxygenation during the intraoperative management of cardiopulmonary bypass and carotid endarterectomy (8,10,11,18). It has also been investigated for use in the management of adult and neonatal ischemic brain injury (1,3,6,14) and traumatic brain injury (22).…”
mentioning
confidence: 99%